Effect of Low Intensity Transcranial Ultrasound Stimulation on Neuromodulation in Animals and Humans: An Updated Systematic Review - Kim, Taewon; Park, Christine; Chhatbar, Pratik Y.; Feld, Jody; Mac Grory, Brian; Nam, Chang S.; Wang, Pu; Chen, Mengyue; Jiang, Xiaoning; Feng, Wuwei (Frontiers in Neuroscience, 2021)
Background: Although low-intensity transcranial ultrasound stimulation (LI-TUS) has received more recognition for its neuromodulation potential, there remains a crucial knowledge gap regarding the neuromodulatory effects of LI-TUS and its potential for translation as a therapeutic tool in humans. Objective: In this review, we summarized the findings reported by recently published studies regarding the effect of LI-TUS on neuromodulation in both animals and humans. We also aim to identify challenges and opportunities for the translation process. Methods: A literature search of PubMed, Medline, EMBASE, and Web of Science was performed from January 2019 to June 2020 with the following keywords and Boolean operators: [transcranial ultrasound OR transcranial focused ultrasound OR ultrasound stimulation] AND [neuromodulation]. The methodological quality of the animal studies was assessed by the SYRCLE's risk of bias tool, and the quality of human studies was evaluated by the PEDro score and the NIH quality assessment tool. Results: After applying the inclusion and exclusion criteria, a total of 26 manuscripts (24 animal studies and 2 human studies) out of 508 reports were included in this systematic review. Although both inhibitory (10 studies) and excitatory (16 studies) effects of LI-TUS were observed in animal studies, only inhibitory effects have been reported in primates (5 studies) and human subjects (2 studies). The ultrasonic parameters used in animal and human studies are different. The SYRCLE quality score ranged from 25% to 43%, with a majority of the low scores related to performance and detection bias. The 2 human studies received high PEDro scores (9/10). Conclusion: LI-TUS appears to be capable of targeting both superficial and deep cerebral structures to modulate cognitive or motor behavior in both animals and humans. Further human studies are needed to more precisely define the effective modulation parameters and thereby translate this brain modulatory tool into the clinic.